Interbrain Synchrony in the Expectation of Cooperation Behavior: A Hyperscanning Study Using Functional Near-Infrared Spectroscopy - Zhang, Mingming; Jia, Huibin; Zheng, Mengxue (Frontiers in Psychology, 2020)
Expectation of others’ cooperative behavior plays a core role in the economic cooperation. However, the dynamic neural substrate of expectation of cooperation (hereafter EOC) are rarely known. To fully understand the EOC behavior in more natural social interactions, the present study employed a functional near-infrared spectroscopy (fNIRS) hyperscanning technique to simultaneously measure pairs of participants’ brain activations in a modified prisoner's dilemma game (PDG). The neural data analysis revealed that the high-incentive condition and defective expectation elicited higher interbrain synchrony (IBS) in the inferior frontal gyrus (IFG). Meanwhile, the IBS in the IFG may play as a role of mediation in relationship between empathy and EOC behavior in female dyads. These results indicate the involvement of the human mirror neuron system (MNS) in the EOC behavior, also demonstrate the modulation effect of social environmental cue and individual differences. Moreover, compared with separate expectation stage, female dyads exhibited a higher IBS value of cooperative expectation in the dorsal medial prefrontal cortex (DMPFC) in the team expectation stage. These sex effects thus providing presumptive evidence that females are more sensitive of environmental cues, also suggest that during economic social interaction, females’ EOC behavior depend on more social cognitive abilities. Overall, all these results raise intriguing topics for future research of human cooperative behaviors.